2019
DOI: 10.3390/atmos10060347
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Characterization of Land Cover in Urban Environments: Determining the Importance of Including Obscured Impervious Surfaces in Urban Heat Island Models

Abstract: Urban heat islands (UHI) increase summer temperatures and can threaten human well-being during extreme heat events. Since urbanization plays a key role in UHI development, accurate quantification of land cover types is critical to their identification. This study examines how quantifying land cover types using both two- and three-dimensional approaches to land cover quantification affects an UHI model’s explanatory power. Two-dimensional approaches treat tree canopies as a land cover, whereas three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…With rapid development and the intensification of urbanization, the scale of cities has expanded rapidly and urban buildings tend to be denser, which brings more pressure on the population, transportation, and industrial production, and causes severe damage to the ecological environment of the entire city. Urban Heat Islands (UHIs) are attracting more and more attention, especially in summer, as scorching hot temperatures have severely affected people's lives and work [1][2][3]. To date, researchers all over the world have carried out much research on UHIs.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid development and the intensification of urbanization, the scale of cities has expanded rapidly and urban buildings tend to be denser, which brings more pressure on the population, transportation, and industrial production, and causes severe damage to the ecological environment of the entire city. Urban Heat Islands (UHIs) are attracting more and more attention, especially in summer, as scorching hot temperatures have severely affected people's lives and work [1][2][3]. To date, researchers all over the world have carried out much research on UHIs.…”
Section: Introductionmentioning
confidence: 99%
“…GIS-based methodology to evaluate green roofs and green urban areas 9 [4][5][6][7][8][9][10][11][12] Outdoor thermal comfort: UHI mitigation strategies and thermal comfort indexes 20 [2,4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Energy savings and Indoor thermal comfort from Green roofs 5 [1,[31][32][33][34] 2.…”
Section: No Of Papers Sourcementioning
confidence: 99%
“…As already mentioned, green areas improves the aesthetic value of urban context reducing the UHI effect and achieving comfortable microclimate and climate conditions [13][14][15][16][17][18]. The urbanization plays a key role in UHI expansion, an analysis of land cover types is critical for the outdoor spaces assessment in order to improve the thermal comfort, liveability and air quality of an urban environment [19]. Outdoor thermal comfort varies according to morphological context [16,17], and any increase in the environmental air temperature is influenced to a great extent by the thermal characteristics of buildings and urban surfaces [20].…”
Section: Outdoor Thermal Comfort: Uhi Mitigation Strategies and Thermmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, later on, Chatterjee et al [18] updated and improved the existing models and realized the simulation of the indoor-outdoor heat transfer and exchange process of urban buildings with the dynamic man-made heat emission taken into consideration; the constructed energy balance equation and the estimated temperature field parameters were more accurate and complete; then, with a medium-sized city as an example, the city's thermal environment evolution in the process of urbanization was quantitatively analyzed. Since there are often contradictions between the time and space resolution of high-resolution remote sensing images [19][20][21][22], in response to this problem, Malings et al [23] proposed an urban-space downscaling thermal environment analysis method, and achieved LST retrieval and space downscaling based on the radiation transfer equation method and the Distrad algorithm; and they used actual examples to analyze the change trend of LST in the city under the influence of temporal and spatial changes of underlying surface in the past 5 years. Sabatino et al [24] analyzed the spatial distribution characteristics of abnormal urban thermal blocks based on the results of LST retrieval; by comparing the boundary of builtup areas and the boundary of thermal environment areas, it was found that the two were basically consistent; after that, they employed MLR to conduct correlation analysis on the LST of areas with different land utilization patterns, and finally proposed a quantitative method for mitigating the thermal abnormalities of high-temperature blocks.…”
Section: Introductionmentioning
confidence: 99%